The Jean Freeman Gallery does not exist. - Howard, Christopher (Massachusetts : the MIT Press, 2018)
Bochner, Mel ; Chicago, Judy ; Ono, Yoko ; Ruscha, Ed ; De maria, Walter ; Hutchinson, Peter ; Oppenheim, Dennis ; Fugate-Wilcox, Terry
Conceptuele kunst, New York, 1970-1971
boek